2022
DOI: 10.1001/jamaneurol.2022.2672
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Daily Step Count and Intensity With Incident Dementia in 78 430 Adults Living in the UK

Abstract: ImportanceStep-based recommendations may be appropriate for dementia-prevention guidelines. However, the association of step count and intensity with dementia incidence is unknown.ObjectiveTo examine the dose-response association between daily step count and intensity and incidence of all-cause dementia among adults in the UK.Design, Setting, and ParticipantsUK Biobank prospective population-based cohort study (February 2013 to December 2015) with 6.9 years of follow-up (data analysis conducted May 2022). A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 16 publications
4
89
0
10
Order By: Relevance
“…In this study, walking among the older adults significantly improved health behaviors, and showed that frequent walking has a positive impact on the health of older adults [ 70 ]. According to a UK study, older adults can reduce their risk of developing dementia by 25% if they take 3800 steps/day, and by 50% if they walk 10,000 steps/day [ 71 ]. In addition, it has been found that older adults suffer from chronic diseases of hyperglycemia, and a fixed number of walks per day for many years can effectively control blood glucose [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, walking among the older adults significantly improved health behaviors, and showed that frequent walking has a positive impact on the health of older adults [ 70 ]. According to a UK study, older adults can reduce their risk of developing dementia by 25% if they take 3800 steps/day, and by 50% if they walk 10,000 steps/day [ 71 ]. In addition, it has been found that older adults suffer from chronic diseases of hyperglycemia, and a fixed number of walks per day for many years can effectively control blood glucose [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…We excluded participants with missing covariates and insufficient valid wear days. Monitoring days were considered valid if wear time was greater than 16 h. To be included in analysis, participants were required to have at least three valid monitoring days, with at least one of those days being a weekend day 45,46 . We excluded participants who reported that they cannot walk.…”
Section: Online Contentmentioning
confidence: 99%
“…We excluded participants with missing covariates and insufficient valid wear days. Monitoring days were considered valid if wear time was greater than 16 h. To be included in analysis, participants were required to have at least three valid monitoring days, with at least one of those days being a weekend day45,46 . We excluded participants who reported that they cannot walk.To enable examination of VILPA in our study (brief bouts of nonexercise VPA occurring during daily living), we included only participants who reported no leisure time exercise participation and no more than one recreational walk per week.…”
mentioning
confidence: 99%
“…Recent studies have indicated that regular physical activity can strengthen the immune system with a flattening of the dose response curve at around 500 MET minutes per week corresponding to moderate levels of activity [ 81 ]. Physical activity also decreases the risk of cognitive decline in individuals with unfavorable lifestyle factors [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%